INTEGRASI NILAI-NILAI PENDIDIKAN JASMANI DALAM AL-QUR’AN DAN HADITS PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM - Putri, Lilida; Fadriati (STAI Pelabuhan Ratu, 2024)
Islam is a religion that is very detailed in dealing with the problems of its creatures, Islam regulates all aspects of human life. All aspects of human life have been regulated in Islamic teachings. The Islamic religion not only regulates religious activities but also about physical and spiritual health and social relations in society. Islam also teaches about physical education and various kinds of sports recommended by the Prophet Muhammad. Allah SWT explains everything in the Qur'an and also the hadith of the Prophet Muhammad Saw. This research is to increase knowledge and insight into how the Al-Qur'an and hadith explain a person's physical education in learning Islamic Religious Education. In this research, the library research method is used, also known as literature review, by collecting various sources from previous research, in the form of theories or expert opinions from various books or articles. Physical education in Islamic Religious Education is seen as the development of a student's body and soul to be stronger in carrying out worship to Allah and always trying to get closer to Allah SWT, as well as being able to socialize well with fellow humans in a social environment. In the perspective of Islamic education, physical health can be used to support body strength as a means of carrying out worship to Allah SWT.